Sex Differences of Periaqueductal Grey Matter Functional Connectivity in Migraine - Gecse, Kinga; Baksa, Daniel; Dobos, Dóra; Aranyi, Csaba Sandor; Galambos, Attila; Kocsel, Natália; Szabó, Edina; Kökönyei, Gyöngyi; Emri, Miklós; Bagdy, Gyorgy; Juhasz, Gabriella (Frontiers in Pain Research, 2021)
The existence of “sex phenotype” in migraine is a long-standing scientific question. Fluctuations of female sex hormones contribute to migraine attacks, and women also have enhanced brain activity during emotional processing and their functional brain networks seem to be more vulnerable to migraine-induced disruption compared to men. Periaqueductal grey matter (PAG) is a core region of pain processing and modulation networks with possible sex-related implications in migraine. In our study, sex differences of PAG functional resting-state connectivity were investigated in the interictal state in 32 episodic migraines without aura patients (16 women and 16 men). A significant main effect of sex was detected in PAG connectivity with postcentral, precentral, and inferior parietal gyri, and further differences were found between right PAG and visual areas (superior occipital gyrus, calcarine, and cuneus), supplementary motor area, and mid-cingulum connectivity. In all cases, PAG functional connectivity was stronger in female migraineurs compared to males. However, higher average pain intensity of migraine attacks correlated with stronger connectivity of PAG and middle temporal, superior occipital, and parietal gyri in male migraineurs compared to females. Migraine-related disability is also associated with PAG connectivity but without sex differences. Our results indicate that sex differences in PAG connectivity with brain regions involved in sensory and emotional aspects of pain might contribute to the “sex-phenotype” in migraine. The stronger functional connectivity between PAG and pain processing areas may be a sign of increased excitability of pain pathways even in resting-state in females compared to male migraineurs, which could contribute to female vulnerability for migraine. However, pain intensity experienced by male migraineurs correlated with increased connectivity between PAG and regions involved in the subjective experience of pain and pain-related unpleasantness. The demonstrated sex differences of PAG functional connectivity may support the notion that the female and male brain is differently affected by migraine.